Wound Healing Activities and Potential of Selected African Medicinal Plants and Their Synthesized Biogenic Nanoparticles - Caroline Tyavambiza; Phumuzile Dube; Mediline Goboza; Samantha Meyer; Abram Madimabe Madiehe; Mervin Meyer (Plants, 2021)
In Africa, medicinal plants have been traditionally used as a source of medicine for centuries. To date, African medicinal plants continue to play a significant role in the treatment of wounds. Chronic wounds are associated with severe healthcare and socio-economic burdens despite the use of conventional therapies. Emergence of novel wound healing strategies using medicinal plants in conjunction with nanotechnology has the potential to develop efficacious wound healing therapeutics with enhanced wound repair mechanisms. This review identified African medicinal plants and biogenic nanoparticles used to promote wound healing through various mechanisms including improved wound contraction and epithelialization as well as antibacterial, antioxidant and anti-inflammatory activities. To achieve this, electronic databases such as PubMed, Scifinder® and Google Scholar were used to search for medicinal plants used by the African populace that were scientifically evaluated for their wound healing activities in both in vitro and in vivo models from 2004 to 2021. Additionally, data on the wound healing mechanisms of biogenic nanoparticles synthesized using African medicinal plants is included herein. The continued scientific evaluation of wound healing African medicinal plants and the development of novel nanomaterials using these plants is imperative in a bid to alleviate the detrimental effects of chronic wounds.